(untitled) (Italian Journal of Public Health, 2007)
Background: To integrate health impact assessment (HIA) into existing decision-making processes requires not only methods and procedures but also well-trained experts, aware policy makers and appropriate institutions. Capacity building is the assistance which is provided to entities, which have a need to develop a certain skill or competence, or for general upgrading of performance ability. If a new technique is planned to be introduced there is a need for capacity building with no respect to levels (local, regional, national, international) or sectors (health, environment, finance, social care, education, etc.). As such, HIA is a new technique for most of the new Member States and accession countries of the European Union. Methods: To equip individuals with the understanding and skills needed to launch a HIA or be aware of the availability of this methodology and to access information, knowledge and training, we focused on the organization of workshops in participating countries. The workshops served also as pilot events to test a “curriculum” for HIA; a set of basic topics and presentations had been developed to be tested during workshops. In spite of classical in-class workshops we aimed to organize e-learning events as a way to over come the “busyness” problem of decision makers. Results: Throughout March – October 2006 we organized and ran 7 workshops in Denmark, Turkey, Lithuania, Poland, Bulgaria, Slovak Republic and Hungary. Participants came from the public health sector (141), non-public health decision makers (113) and public health students (100). A concise curriculum was developed and tested during these workshops. Participants developed a basic understanding of HIA, skills to develop and use their own screening tools as well as scoping.Within the workshop in Denmark we tested an online, real-time Internet based training method; participants highly welcomed this method as it allowed them to take part in training from their workplace, and it did not disturb their daily work. Conclusions: The workshops set a very good baseline for the introduction of HIA in participating countries. The training documents are being translated into their national languages and will be posted on the national HIA web pages of the participating countries. Participating countries have expressed an interest in continuing on with similar workshops on specific issues related to HIA, providing more in-depth training.